Impacts of climate variability and changing land use/land cover on River Mpanga flows in Uganda, East Africa - Onyutha, Charles; Turyahabwe, Catherine; Kaweesa, Paul (Environmental Challenges, 2021)
We analyzed River Mpanga Catchment (RMC) land use/land cover (LULC) types based on Landsat images for 2000, 2008 and 2014. Soil and Water Assessment Tool (SWAT) was driven by daily meteorological data from 2000 to 2011 to investigate impacts of LULC changes on river flow variation. In 2000, 2008, and 2014, cropland covered 33.0%, 69.1%, and 72.2% of RMC area, respectively. However, the fractions of the RMC area covered by grassland in 2000, 2008, and 2014 were 39.4%, 12.5%, and 10.4%, respectively. The portion of RMC area covered by human settlement increased from 0.2% in 2000 to 0.5% by 2014. RMC was characterized by increasing trends in annual rainfall and river flows. SWAT calibration and validation at daily scale over the periods 2000–2005 and 2006–2011 yielded Nash Sutcliffe Efficiency of 0.77 and 0.75, respectively. Contribution from transitions in LULC types to river flow changes over the period 2000–2008 was 7.65%. Generally, 70.46% of the total river flow variation was contributed by climate variability in terms of changes in climatic conditions. However, 21.89% of the total river flow variance remained unexplained and this could be attributed to other factors not considered in this study including extra impacts of human activities such water abstractions for agricultural, industrial and domestic needs. These findings are important for planning predictive land and water resources management amidst impacts of climate variability and human activities on water resources.
Keywords: SWAT; Land use/land cover (LULC) changes; Hydrological modeling; River Mpanga catchment partitioning river flow drivers; Uganda